Laparoscopy in acute and chronic pelvic inflammatory disease - Siu, Alejandro (2015)
We review the use of laparoscopy in the diagnosis and treatment of acute and chronic pelvic inflammatory disease. Use decision, approach and management will depend on case presentation circumstances, varying from drainage to salpingectomy and histerectomy. We emphasize on pre, intra y post operative care.